2021
DOI: 10.7150/jca.50509
|View full text |Cite
|
Sign up to set email alerts
|

CAR-T cells for Colorectal Cancer: Target-selection and strategies for improved activity and safety

Abstract: Chimeric antigen receptor-T (CAR-T) cell immunotherapy is a novel method that is genetically engineered to recruit T cells against malignant disease. Administration of CAR-T cells has led to progress in hematological malignancies, and it has been proposed for solid tumors like colorectal cancer (CRC) for years. However, this method was not living up to expectations for the intrinsic challenges posed to CAR-T cells by solid tumors, which mainly due to the lacking of tumor-restricted antigens and adverse effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 120 publications
(137 reference statements)
0
20
0
Order By: Relevance
“…This approach has shown promise in hematological malignancies [ 26 , 27 ], and it has also been advocated for solid tumors. However, there are no CAR-T cell treatments currently approved for CRC despite several studies that have entered clinical trials as a result of ongoing fundamental research efforts [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach has shown promise in hematological malignancies [ 26 , 27 ], and it has also been advocated for solid tumors. However, there are no CAR-T cell treatments currently approved for CRC despite several studies that have entered clinical trials as a result of ongoing fundamental research efforts [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Costimulatory molecules are often administered with engineered T cells, including CD28 or 4-1BB (CD137) [ 92 ]. Low efficacy due to a lack of tumor-specific antigens and adverse events after CAR-T treatment of patients with solid tumors necessitates new approaches including the addition of immune-activating molecules on CAR-T cells, regional administration, bispecific engagers, and optimization of CAR structure [ 93 ]. Very few clinical studies evaluating TCR T cells are underway, but one ongoing trial is investigating the use of TCRs that were cloned from neoepitope-targeting CD8+ cells in the patient’s blood for treatment of solid tumors [ 94 ].…”
Section: Colorectal Cancer Response To Immunotherapymentioning
confidence: 99%
“…CAR-T cell therapy has also been explored in the setting of CRC. CAR-T cells can be manipulated to target a series of tumor-associated antigens (TAAs) highly expressed by CRC tumors, most notably carcinoembryonic antigen CEA [122]. A phase I clinical trial (NCT02349724) indicated that CEA CAR-T cell therapy has some efficacy in mCRC patients with CEA positive tumors, with an acceptable toxicity profile.…”
Section: Adoptive Cell Transfermentioning
confidence: 99%